2019
DOI: 10.1007/s42729-019-00090-3
|View full text |Cite
|
Sign up to set email alerts
|

Zn-DTPA-HEDTA-EDTA Application: a Strategy to Improve the Yield and Plant Quality of a Barley Crop While Reducing the N Application Rate

Abstract: Over-use of N fertilization has been common in order to obtain the highest possible grain yield. We investigated the efficiency of combining the application of N and ZnCHE (Zn-DTPA-HEDTA-EDTA). Different rates (30, 60, or 90 kg ha −1) and sources [pig slurry(PS) or urea] of N and rates of ZnCHE (0, 0.5, 1, or 1.5 kg ha −1) were applied to a barley crop. Nitrogen fertilization combined with soil Zn applications had a significant interaction on various plant parameters (grain protein concentration, yield, Zn upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Several authors have studied nutrient mobility within plants by calculating TFs ( Zhang et al., 2019 ). When TF is calculated as the ratio between the nutrient concentration in the shoot of the plant and nutrient concentration in the root of the plant, a high TF value indicates high nutrient mobility and the possibility of accumulating large amounts of nutrients in the aerial part of plants ( Alloway 2013 ; Almendros et al., 2019 ; Intawongse and Dean 2006 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have studied nutrient mobility within plants by calculating TFs ( Zhang et al., 2019 ). When TF is calculated as the ratio between the nutrient concentration in the shoot of the plant and nutrient concentration in the root of the plant, a high TF value indicates high nutrient mobility and the possibility of accumulating large amounts of nutrients in the aerial part of plants ( Alloway 2013 ; Almendros et al., 2019 ; Intawongse and Dean 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…Different authors have studied the effect on plant N concentration of the application of traditional Zn sources, such as ZnO, ZnSO 4 , Zn (NO 3 ) 2 , natural complexes (Zn-lignosulphonate, Zn-amino acids and Zn-gluconate) or synthetic Zn chelates as Zn-DTPA-HEDTA-EDTA to cereals ( Almendros et al., 2019 ; Gonzalez et al., 2019b ; Kutman et al., 2011 ). In general, the results of these studies showed positive responses in Zn and N concentrations in plants with increasing Zn application rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were in line with those reported by Almendros et al. (), who suggested that the application of N in the form of urea or pig manure resulted in an increase in barley grain Fe concentrations. The transfer of the Fe cation from the rhizosphere to the grain is dependent on several different proteins and could be enhanced by N fertilization ( Palmer and Guerinot , ).…”
Section: Discussionmentioning
confidence: 99%
“…These chelates should be applied at low rates to lessen the costs of Zn fertilizerson one hand and avoid further environmental pollution risks on the other hand (Demetrio et al, 2016;Abbas and Abdelhafez, 2013). It may also decrease the needed amounts of N-fertilizers for grown plants (Almendros et al, 2019).…”
Section: Hassan H Abbas Et Almentioning
confidence: 99%